Pendampingan Pembuatan Proposal PKM Berbasis Pedoman dan Cara Pengelolan Sistem Belmawa - Setyaningsih, Gustin; Seno, Axel Sandi; Ramadhan, Rifqi Falih; Pribadi, Prayoga; Setiawan, Ito; Yunita, Ika Romadoni (Universitas Pahlawan Tuanku Tambusai, 2025)
After observing the PKM proposal, there are still many proposals that do not comply with the writing guidelines such as attachments, bibliography, budget plans and basic things such as paper size, margins, fonts do not comply with the guidelines. From this case, it becomes one of the problems why very few proposals pass from Amikom Purwokerto University. The PKM proposal assessment consists of 2 stages. The first stage is administrative selection and the second stage is substance selection. Based on interviews with national PKM reviewers, almost 60% of all PKM proposals submitted failed at the administrative selection stage. In addition, in the process of uploading PKM proposals to the system, many students do not understand the stages of filling in the system. The purpose of this assistance is to reduce the error rate of PKM proposals made by students. The stages of implementing assistance include assistance in making proposals, assistance in managing the Simbelmawa system, evaluation and discussion. The results of the assistance are that many student proposals are in accordance with the 2025 PKM guidelines.